Home-physiotherapy for a post-COVID-19 patient with PICS: Case report - Wilches-Luna, Esther Cecilia (2023)
We describe a case of home-physiotherapy intervention supported by telemedicine for a post-COVID-19 patient with impairments associated with PICS. A 42-year-old male patient that was diagnosed with COVID-19 and stayed for 22 days in an Intensive Care Unit, developed impairments associated with PICS and was assigned home-physiotherapy sessions supported by telemedicine. A physiotherapist performed the intervention on the patient at home, following the instructions of another physiotherapist more experienced in post-COVID-19 patients and that was in another city. The physiotherapists were connected through a video call. The muscle strength in the four limbs increased from 3- to 4+, the dyspnea improved from 8 to 0, the functionality from 50 to 95/100, the anxiety from 9 to 6 and the depression from 9 to 1; SF36V2 domains improved 60%, except for limitations due to physical problems. Four weeks of home physiotherapy helped to reduce symptoms, and to improve exercise tolerance as well as daily living activities and quality of life. The home physiotherapy intervention used in this case, helped the post-COVID-19 patient to improve impairments associated with PICS, nevertheless, further studies with a longer follow-up period are needed to validate our results.